The Sunday Times Garden DIY - Pub. by The Sunday Times (London Ted Smart, 2001)
This manual contains information needed to plan, construct and maintain a garden space. For the beginner, there are easy to follow instructions on the basics of garden DIY, while there is more experienced material for the experienced gardener. There are details on a range of projects, from laying paths, building fences and summer houses to more decorative ideas such as creating a water feature or installing outdoor lighting. The book contains photographs and illustrations as well as design plans.
Includes Colored Illustrarions and Index
Keywords: Gardens -- Design